Influência de atividades antrópicas sobre a salinização da água em área de dunas no Município de Guamaré RN - Ferreira, Douglisnilson de Morais (2011)
The municipality of Guamaré is located on the north coast of RN, Salineira zone, with a land area of 259 km2 and a population of approximately 12,500 inhabitants (IBGE, 2010). Presents strong morphological instability caused mainly by the influence of human activities in the region. The present study aims to assess the existing levels of salts in the springs of the region, by evaluating the electrical conductivity, pH, salinity, chlorides, hardness, calcium, magnesium and heavy metals in the water. The collection and analysis methods adopted in the survey are based on APHA (2005). The electrical conductivity, salinity and chloride behaved similarly throughout the study. Some points suffered the direct effect of the salt ponds and others. Given the existence of a drainage ditch between the saline and monitored region, there was little change in the environment, including the native vegetation. The opposite situation occurred in farms where the region is fully committed local vegetation and water holes and wells used in the past for domestic use are practically disabled (high salt content). In Rio Miassaba formation of an estuary is reversed, with the farther out from the sea showing higher salt concentracions, which may be associated with the discharge of organic matter and natural evaporation rate. In periods of no rainfall had a few points higher than the levels of salts found in seawater and may be associated with high evaporation in the region. Detected a positive factor is the high resilience and reducing salt, after periods of rainfall incidence